How Does Music-Message Congruency in Online Video Advertisements Enhance Consumers’ Behavior Intentions? A Serial Multiple Mediator Model - Yongzhong Yang; Ruo Yang; Xiaoting Song; Yunyan Tang (IEEE Access, 2021)
This study provides new insights into the influence of music-message congruency on behavior intentions. A serial multiple mediation model in which the relationship between music-message congruency and behavior intentions is sequentially mediated by arousal and brand trust was constructed and tested. A total of 261 valid questionnaires were obtained after participants watched the online video advertisements. PROCESS macro for SPSS was then used to test the serial mediation hypotheses. The results showed that: (1) music-message congruency has a positive effect on behavior intentions; (2) brand trust plays a partial mediating role between music-message congruency and behavior intentions, and (3) arousal and brand trust mediate the relationship between music-message congruency and behavior intentions sequentially.